5D Cubic B-Spline Interpolated Compensation of Geometry-Based Errors in Five-Axis Surface Machining. Issue 3 (3rd May 2016) - Bhuiya, Md Shafayet H.; Tutunea-Fatan, O. Remus
ABSTRACT: Linear interpolation constitutes the most common type of interpolation currently employed in five-axis computer numerically-controlled (CNC) surface machining. However, despite its popularity, this type of interpolation constitutes one of the primary causes of the significant decreases in the overall productivity and accuracy of the five-axis machining process. This decline in efficiency can be explained – at least in part – through the discontinuities in velocity that are present in the joint space as well as through the geometry-based errors that are an expression of the unsynchronized translational and rotational motions associated with machine tool kinematics. To address these issues, the present study proposes an alternate interpolation scheme based on a 5D cubic B-Spline whose knot values are determined by means of ideal joint trajectories to be followed. Two supplementary end conditions are then added to make the problem at hand determined in terms of control point position. The implementation of the proposed technique revealed that in addition to its inherent C 1 continuity, the proposed 5D B-Spline interpolation enables significant reductions of the machining errors along the intended tool path.